2022
DOI: 10.3390/antiox11091664
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Dietary Selenium Supplementation on Blood Antioxidant and Metabolic Status of Ewes and Their Lambs

Abstract: This study investigated the effect of dietary selenium supplementation (organic and inorganic) of late-gestation ewes on blood selenium concentrations and metabolic and antioxidant status indicators in ewes and their lambs. In addition, the efficacy of selenium transfer from ewes to lambs during the suckling period was determined. The study was conducted on 30 Merinolandschaf ewes and their lambs and lasted four months. The feed mixture of the control group (group I) contained no added selenium, while the feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Gong et al [22] found increased GSH-Px activity and total antioxidant capacity in dairy cows that were offered 0.3 mg selenised yeast/kg for 60 days as compared to cows fed sodium selenite at the same level. Novoselec et al [51] reported increased GSH-Px and SOD activity and lower MDA levels in the blood of late-gestation Se-fed ewes compared to the unsupplemented ones [52]. Likewise, lower MDA values, higher GSH-Px activity, and higher total antioxidant capacity were reported in the blood of pregnant goats that were supplemented with Se.…”
Section: Supplementation Of Ly and Postbiotics Blend Triggered Antiox...mentioning
confidence: 92%
“…Gong et al [22] found increased GSH-Px activity and total antioxidant capacity in dairy cows that were offered 0.3 mg selenised yeast/kg for 60 days as compared to cows fed sodium selenite at the same level. Novoselec et al [51] reported increased GSH-Px and SOD activity and lower MDA levels in the blood of late-gestation Se-fed ewes compared to the unsupplemented ones [52]. Likewise, lower MDA values, higher GSH-Px activity, and higher total antioxidant capacity were reported in the blood of pregnant goats that were supplemented with Se.…”
Section: Supplementation Of Ly and Postbiotics Blend Triggered Antiox...mentioning
confidence: 92%
“…These data are displayed to promote the investigation Se concentrations are allowed to be consumed, but avoid high doses that lead to toxicity [31] . On the other hand, ewes that are in the late stages of pregnancy may undergo alterations by using Se nutritional supplements, which enhance oxidative stability and elevate the level of glutathione peroxidase in ewes' and lambs' blood [32] . Lambs, as a consequence, produce more growth and have a stronger immune system than dams and lambs from poor Se regions [20] .…”
Section: Introductionmentioning
confidence: 99%
“…In ewes and lambs, organic Se increased blood Se levels and antioxidant indices to a greater extent than inorganic Se. Organic Se is also readily transferred from ewes to their lambs and promotes the overall health of the latter ( Josip et al, 2022 ). Compared to inorganic Se, then, organic Se more effectively promotes animal growth, development, and production performance, improves meat quality, and enhances the antioxidant capacity of the body.…”
Section: Introductionmentioning
confidence: 99%